2022
DOI: 10.3390/ijms231911299
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Binding Propensity of Human SHIP2 SH2 to Oncogenic CagA Isoforms from Helicobacter pylori

Abstract: SHIP2 is a multi-domain inositol 5-phosphatase binding to a variety of phosphotyrosine (pY)-containing proteins through its SH2 domain, so as to regulate various cell signaling pathways by modulating the phosphatidylinositol level in the plasma membrane. Unfavorably, Helicobacter pylori can hijack SHIP2 through the CagA protein to induce gastric cell carcinogenesis. To date, the interaction between SHIP2 and CagA was not analyzed from a structural point of view. Here, the binding of SHIP2-SH2 with Tyr-phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In GC, SHIP2 is frequently expressed depressedly and has an antagonistic effect on tumorigenesis and proliferation in gastric cancer [ 14 ]. However, H. pylori can hijack SHIP2 through intracellular CagA to induce gastric cell carcinogenesis [ 36 ]. In this study, we found that by interacting with CagA, SHIP2 induces cell migration, invasion, and IL-8 secretion, thereby contributing to the higher oncogenicity of CagA E than that of CagA W .…”
Section: Discussionmentioning
confidence: 99%
“…In GC, SHIP2 is frequently expressed depressedly and has an antagonistic effect on tumorigenesis and proliferation in gastric cancer [ 14 ]. However, H. pylori can hijack SHIP2 through intracellular CagA to induce gastric cell carcinogenesis [ 36 ]. In this study, we found that by interacting with CagA, SHIP2 induces cell migration, invasion, and IL-8 secretion, thereby contributing to the higher oncogenicity of CagA E than that of CagA W .…”
Section: Discussionmentioning
confidence: 99%